2022
DOI: 10.1108/cms-12-2021-0508
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of knowledge workers’ adaptive perfectionism on taking charge

Abstract: Purpose This study aims to explore the mechanisms of adaptive perfectionism on employees’ taking charge (TC), the mediating role of work family enrichment and the moderating role of perceived organizational support (OS) in the relationship between adaptive perfectionism and employees’ TC. Design/methodology/approach This study is based on 305 knowledge workers working in diverse organizations in China to examine the hypotheses. Findings The results showed that adaptive perfectionism had a significant posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The study's second hypothesis is related to the relationship between workplace incivility and psychological detachment and it has been identified that workplace incivility significantly correlated with Perfectionist leaders psychological detachment. The victims of a leader's incivility detach themselves from work because of their ego depletion (Wei and Zhang, 2022). Employees who encounter uncivil behavior from their leaders psychologically detach themselves from work-related activities (Anjum et al, 2021).…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…The study's second hypothesis is related to the relationship between workplace incivility and psychological detachment and it has been identified that workplace incivility significantly correlated with Perfectionist leaders psychological detachment. The victims of a leader's incivility detach themselves from work because of their ego depletion (Wei and Zhang, 2022). Employees who encounter uncivil behavior from their leaders psychologically detach themselves from work-related activities (Anjum et al, 2021).…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%